2021
DOI: 10.1001/jamanetworkopen.2021.0045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cigarette Constituent Messages With Engagement Text on Intention to Quit Smoking Among Adults Who Smoke Cigarettes

Abstract: Key Points Question Do cigarette constituent messages with US Food and Drug Administration sourcing and engagement text (ie, encouragement to quit) increase intentions to quit more than cigarette constituent messages alone or control messages? Findings In this randomized clinical trial of 789 adults who smoke cigarettes, participants assigned to the constituent plus engagement and constituent-only message conditions demonstrated increased quit intentions fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The hypothetical product standard statements tested in this study linked a reduced level of an HPHC with reduced cases of a health outcome, which may discourage adults and adolescents from wanting to use tobacco products, a possibility that could be further explored. In a randomized controlled trial, participants’ intentions to quit smoking increased after viewing statements about the chemicals in cigarette smoke, suggesting that information about HPHCs can influence behavior ( Goldstein et al, 2021 ). However, it is still unclear how statements about reducing the amount of HPHCs in tobacco products would influence behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothetical product standard statements tested in this study linked a reduced level of an HPHC with reduced cases of a health outcome, which may discourage adults and adolescents from wanting to use tobacco products, a possibility that could be further explored. In a randomized controlled trial, participants’ intentions to quit smoking increased after viewing statements about the chemicals in cigarette smoke, suggesting that information about HPHCs can influence behavior ( Goldstein et al, 2021 ). However, it is still unclear how statements about reducing the amount of HPHCs in tobacco products would influence behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrates that this theme is an effective strategy for increasing perceptions of effectiveness. Previous research in tobacco communication has identified that communicating about specific constituents is promising ( Cho et al, 2018a , Cornacchione et al, 2016 , Goldstein et al, 2021 , Hall et al, 2014 , Lazard et al, 2018 , Sutfin et al, 2019 , Wiseman et al, 2016 ), but little is known about communicating about toxicity more broadly. It is possible that warnings that communicate about toxicity more broadly, rather than about a specific constituent, might be more effective because the language is universally understood, as opposed to individual constituents, which likely require a higher level of understanding.…”
Section: Discussionmentioning
confidence: 99%
“…For secondhand smoke effects , we created two warnings about harm to others and harm to children and included a general statement about secondhand smoke, reflecting similar themes as an existing cigar warning. For the chemicals/constituents statements, we selected four chemicals that performed well in previous research (arsenic, lead, formaldehyde, uranium) and another (carbon monoxide) that has appeared in other tobacco warnings ( Goldstein et al, 2021 ). Finally, for the statements about toxicity , we created two statements about cigar smoke being poisonous and toxic, similar to warnings used in other countries.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation